EFFECT OF ADDITIONAL TRISODIUM PHOSPHATE 2% AS A RETARDER TO DIMENSIONAL STABILITY TESTS DENTAL MATERIAL ALGINATE AFTER HARDENING (PENGARUH PENAMBAHAN TRISODIUM FOSFAT 2% SEBAGAI RETARDER TERHADAP UJI STABILITAS DIMENSI BAHAN CETAK ALGINAT SETELAH MENGERA - Zwista Yulia Dewi; Rachman Ardan; Shinta Damayantie (Fakultas Kedokteran Gigi Unjani, 2022)
The alginate moulding material is a negative mold of the teeth and oral cavity tissue. The alginate molding material is hydrophilic and is used as a pre-elimination mold to a custom tray for a more accurate second mold. The dimensional stability of the alginate mold is essential for the success of making a precise mold model. Changes in alginate dimensions are related to the contraction during the hardening process of the alginate molding material or the setting time. The addition of Trisodium Phosphate (TSP) is known to prolong the hardening time of alginates by slowing down the reaction of alginate salts and calcium sulfate. The purpose of this study was to compare the dimensional stability test of the alginate molding material with the addition of 2% trisodium phosphate and those without 2% trisodium phosphate after hardening. This research is pure laboratory experimental research. Alginate was divided into two groups: the group according to the manufacturer's provisions and the group added with 2% trisodium phosphate. The results of this study were analyzed using the unpaired T-test, and the results showed a p-value <0.05, namely (0.00 <0.05), so there was a significant difference in the dimensional stability of alginate without TSP 2% with the addition of TSP 2%. This study showed that the addition of 2% TSP improved dimensional stability in the group with the addition of 2% TSP. DOI : 10.54052/jhds.sd22.p221-235